2013
DOI: 10.4137/mbi.s12996
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Streptococcus Pyogenes Isolated from Respiratory Tract Infections in Dakar, Senegal

Abstract: Group A Streptococcus (GAS) is one of the major causes of respiratory tract infections. The objectives of this study were to identify isolates of S. pyogenes obtained from respiratory tract infections, and to assess their susceptibility to several antibiotics. A total of 40 strains were isolated and their susceptibility to 17 antibiotics was tested using a standard disk diffusion method. The minimum inhibitory concentrations (MICs) were determined using the E-test. All isolates were sensitive to β-lactam antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
32
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 29 publications
15
32
3
3
Order By: Relevance
“…All Streptococcus pyogenes isolated in this study were sensitive to Clindamycin and Vancomycin while they were absolutely resistant to Levofloxacin and Erythromycin. Very similar antibiotic sensitivity patterns of Streptococcus pyogenes are reported earlier [21,22]. The majority of Streptococcus pneumoniae were resistant against Co-Trimoxazole, Clindamycin, and Erythromycin.…”
Section: Discussionsupporting
confidence: 78%
“…All Streptococcus pyogenes isolated in this study were sensitive to Clindamycin and Vancomycin while they were absolutely resistant to Levofloxacin and Erythromycin. Very similar antibiotic sensitivity patterns of Streptococcus pyogenes are reported earlier [21,22]. The majority of Streptococcus pneumoniae were resistant against Co-Trimoxazole, Clindamycin, and Erythromycin.…”
Section: Discussionsupporting
confidence: 78%
“…We evaluated local antibiotic concentrations to determine whether the concentrations contained in the eluent exceeded the MIC of common infecting pathogens and concentrations in the serum were also evaluated for all subjects [44][45][46][47]. Table 3 lists the results.…”
Section: Resultsmentioning
confidence: 99%
“…Tetracycline (30µg) was sensitive to 7 isolates (33.3%) out of total 21 isolates and resistant in case of 14 isolates (66.7%) respectively. Some previous studies also showed high rate of tetracycline resistance conducted by Jasir A et al [28] showing 42% resistance by standard disc diffusion method as well as 100% resistance shown by study conducted by Camara M et al [29] and 18% resistance by Devrim Dunda et al [30] respectively.…”
Section: IImentioning
confidence: 89%